Pengaruh Konsistensi Cita Rasa dan Harga Produk HIMAJAS Bagi Konsumen untuk Melakukan Pembelian Ulang - Maitsa Nayla Faiha (International Journal Administration, Business & Organization, 2022)
This research article was prepared with the aim of finding out and analyzing the effect of the consistency of taste and price of HIMAJAS processed chicken products for consumers to make repeat purchases. The research method used is descriptive quantitative. The population in this study were all consumers of HIMAJAS. Data collection techniques were carried out by distributing questionnaires (gform) to 110 respondents. The analytical method used is Validity and Reliability Test, Normality, Simple Regression, and Hypothesis Testing. The results showed that the consistency of taste and product price had a positive effect on consumers' repurchase interest in HIMAJAS food products. Consistency of consumer taste and product price contributed 48.7% to consumers' repurchase interest.